Cognitive and behavioral impairment in mild hyperphenylalaninemia - S Gülin Evinç; Ferhunde Öktem; Turgay Coskun; Ayşegül Tokatlı; Ali Dursun; Berrak Bilginer-Gürbüz; Yamaç Karaboncuk; Yılmaz Yıldız; Dilşad Foto-Özdemir; Emine Pektaş; H Serap Sivri (The Turkish Journal of Pediatrics, 2018)
As elevated phenylalanine (Phe) is detrimental to brain functions, determining a safe upper limit of blood Phe is important for initiation of treatment plans and setting Phe targets in hyperphenlalaninemic patients. It is accepted that Phe levels below 360 μmol/L does not impair brain function and hence does not require treatment. Therefore, we aimed to compare cognitive functions and attention-related problems among healthy children and untreated patients with hyperphenylalaninemia (HPA). This study included 41 hyperphenylalaninemic patients (`all HPA group`) aged 6-16 years with untreated blood Phe between 240 and 600 μmol/L and 29 healthy controls. `All HPA group` was further divided into 2 subgroups according to their lifetime median blood Phe levels as `Phe 360-600 μmol/L` and `Phe 240-360 μmol/L` groups. Wechsler Intelligence Scale for Children-IV (WISC-IV), Conners` Continuous Performance Test (CPT), Strength and Difficulties Questionnaire (SDQ) and Schedule for Affective Disorders and Schizophrenia for School-Age Children: Present and Lifetime Version (K-SADS-PL) were performed as a comprehensive neurocognitive, attention and behavioral assessment. The study illustrated that `all HPA` patients had significantly lower scores on all WISC-IV indexes compared to controls, except for Working Memory. Both `Phe 360-600 μmol/L` and `Phe 240-360 μmol/L` subgroups had lower Full Scale intelligence quotient (IQ) and Verbal Comprehension scores compared to controls. `All HPA` patients also had longer reaction times and more peer problems than controls, indicating attention deficits and behavioral problems. Since the results demonstrated that children with untreated Phe levels between 240-360 μmol/L are at higher risk for cognitive and attention-related problems, lowering the `safe` upper Phe level should be considered.